Talking the wrong talk? - Paul Geraghty (Asia Pacific Network, 2001)
If a serious commitment were made to produce a quality Fijian daily, I don't doubt that it would soon outsell all the English ones. Next time anyone in the Fiji media suggests that a major problem today is that the Fijian people are so ill-informed, maybe they should question the Fiji media.